Occupational inhalation injury by Hydrogen Sulfide causing multi organ failure –A case study (Bangladesh Critical Care Journal, 2019)
Hydrogen sulfide is a notorious agent known to cause serious injuries in the occupational field. We are going to discussa case of a 20 years old male working in a effluent treatment plant in Savar, Bangladesh who accidentally entered thefume room and was exposed to the toxic gas. He lost consciousness and was brought to our care from a local hospitalafter endotracheal intubation condition. He was found in state of unconsciousness grade III on admission to our ICU.His brain CT scan revealed diffuse cerebral edema. Chest X-ray revealed finding suggestive of diffuse pneumonitis.Cardiology evaluation suggested Toxic cardiomyopathy as his high sensitive Troponin I was very high on admission (2037ng/L). Supportive care was given in the form of mechanical ventilation, antibiotics, anticonvulsant andanti-ischemic medications. Patient regained consciousness on day 10 after admission and gradually improvedclinically. By the end of the month of stay in hospital he was significantly improved.Bangladesh Crit Care J September 2019; 7(2): 113-115